The State of Our Union - Himes, Kenneth R. (Theological studies, 2017)
A national election provides an opportunity to take a reading of the mood and issues in society. The nomination and election of Donald Trump amounted to a political earthquake that disrupted the establishment of a major political party and set a direction for national leadership that remains uncertain. The rise of populism pushed the issue of social class to the foreground in US politics. There were also issues that continue to divide the nation, particularly race. What is the role for the Catholic Church in post-election America?